2019
DOI: 10.3390/su11030655
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure Operation Efficiency and Influential Factors in Developing Countries: Evidence from China

Abstract: The development of sustainable infrastructure has been identified as one of the seventeen sustainable development goals by the United Nations. Keeping the operation of infrastructure sustainable in terms of economy becomes a major challenge in developing countries. The objective of this research is to evaluate the operation efficiency of the expressway and explore the key influential factors. This research took expressway mileage as the physical output and evaluated the operation efficiency of the expressway c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…e results showed that toll road operations were inefficient, which is consistent with the conclusion of Wei et al [21]. It should be noted that there is a significant difference in the efficiency among the eastern, central, and western regions.…”
Section: Discussion Of Operational Efficiencysupporting
confidence: 89%
See 3 more Smart Citations
“…e results showed that toll road operations were inefficient, which is consistent with the conclusion of Wei et al [21]. It should be noted that there is a significant difference in the efficiency among the eastern, central, and western regions.…”
Section: Discussion Of Operational Efficiencysupporting
confidence: 89%
“…As a nonparametric performance evaluation method, Slacks-Based Measure (SBM) model has been widely used in the evaluation of the operational efficiency of toll roads and other infrastructures [21]. e SBM model takes the slack variable into account in the objective function and overcomes the deficiency of the traditional DEA model's radial distance function and its measurement results closer to reality [45].…”
Section: Sbm Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…e development mode, dilemma, and reform path of China's toll highways have become the focus of world attention [2]. Wei et al [3] stated that the operational efficiency of toll highways is the key to reducing operating costs and achieving sustainable infrastructure. Xu et al [4] thought that the poor operational efficiency is the main problem of the supply side of toll highway industry, and the development of toll highways should be transformed from scale expansion to quality and efficiency improvement.…”
Section: Introductionmentioning
confidence: 99%